Mapping patient pathways and estimating resource use for point of care versus standard testing and treatment of chlamydia and gonorrhoea in genitourinary medicine clinics in the UK. Issue 7 (23rd July 2014) - Adams, Elisabeth J; Ehrlich, Alice; Turner, Katherine M E; Shah, Kunj; Macleod, John; Goldenberg, Simon; Meray, Robin K; Pearce, Vikki; Horner, Patrick
Abstract : Objectives: We aimed to explore patient pathways using a chlamydia/gonorrhoea point-of-care (POC) nucleic acid amplification test (NAAT), and estimate and compare the costs of the proposed POC pathways with the current pathways using standard laboratory-based NAAT testing. Design/participants: Workshops were conducted with healthcare professionals at four sexual health clinics representing diverse models of care in the UK. They mapped out current pathways that used chlamydia/gonorrhoea tests, and constructed new pathways using a POC NAAT. Healthcare professionals' time was assessed in each pathway. Outcome measure: The proposed POC pathways were then priced using a model built in Microsoft Excel, and compared to previously published costs for pathways using standard NAAT-based testing in an off-site laboratory. Results: Pathways using a POC NAAT for asymptomatic and symptomatic patients and chlamydia/gonorrhoea-only tests were shorter and less expensive than most of the current pathways. Notably, we estimate that POC testing as part of a sexual health screen for symptomatic patients, or as stand-alone chlamydia/gonorrhoea testing, could reduce costs per patient by as much as £16 or £6, respectively. In both cases, healthcare professionals' time would be reduced by approximately 10 min per patient. Conclusions: POC testing for chlamydia/gonorrhoea in a clinical setting may reduce costs and clinician time, and may lead to more appropriate and quicker care for patients. Further study is warranted on how to best implement POC testing in clinics, and on the broader clinical and cost implications of this technology.